Synthesis of Cu/Ni-based metal organic frameworks from waste PET bottles for wastewater treatment - Cyril O. Ehi-Eromosele; Samuel O. Ajayi; Chijindu N. Nwaturuocha; Joshua O. Talabi (Results in Chemistry, 2025)
In this study, waste polyethylene terephthalate (PET) was depolymerized into terephthalic acid (TPA) using uncatalyzed neutral hydrolysis. The TPA served as a linker source for preparing Cu/Ni-based metal-organic frameworks (MOFs) for the treatment of dye-polluted wastewater. The synthesized MOFs were characterized with TGA, XRD, FT-IR, BET, and SEM. Batch experiments were conducted on the optimal removal of methyl orange (MO) dye pollutants by the prepared Cu/Ni-based MOFs by varying the dye's initial concentration, contact time, and adsorbent dosage. Langmuir, Freundlich, and Tempkin adsorption isothermal models and adsorption kinetics models were evaluated. The maximum adsorption capacity (Qm) of Cu-MOF and Ni-MOF are 925.38 mg/g and 925.93 mg/g, respectively. The Langmuir model best described the MO adsorption on Ni-MOF while the Freundlich and Temkin model isotherm best described the MO adsorption on Cu-MOF. Both adsorbents had excellent fits to the pseudo-second-order kinetics model, with calculated equilibrium adsorption capacity (qe) values of 18.518 mg/g for Ni-MOF adsorption and 3.589 mg/g for Cu-MOF adsorption. The study not only presents a green method to synthesize MOFs but it is also provided a sustainable waste PET and wastewater management technique.